The Influence of Competence, Training and Motivation on the Performance of Employees of the National Coaching & Instructor Professional Certification Agency - Cahaya, Yohanes Ferry; Rahardi, Patrick Dwi; Pujiati, Herni; Erasashanti, Annathasia Puji; Bilqis, Devia Fairus (Goodwood Publishing, 2025)
Purpose: This research was conducted at the National Training and Instructor Professional Certification Institute (LSP Pelatinas) using the path analysis method. Research methodology: The author collected data using a questionnaire with a population of 80 respondents from LSP Pelatinas employees. Respondent samples were taken from the entire population with a total sample of 80 employees. Previously, instrument testing was carried out and, after that, analysis requirements were tested using the normality test, linearity test and homogeneity test. The latter performs hypothetical testing with path analysis. Results: This study investigated the influence of competence, training, and motivation on employee performance at LSP Pelatinas (Indonesian National Coaching and Instructor Professional Certification Institute) using a survey method with path analysis on 80 employees. The research findings confirmed that competence, training, and motivation all have significant positive effects on employee performance, with competence emerging as the most influential factor for enhancing organizational performance and employee motivation. Conclusions: The study demonstrates that competence, training, and motivation all have significant positive effects on employee performance at LSP Pelatinas, with competence being the strongest predictor (contributing 24.2%), followed by motivation (76.4%), while these three variables collectively explain 95.7% of the variance in employee performance. Limitations: The research was constrained by limited references on similar studies within LSP Pelatinas context, restricted research scope, reliance solely on Google Forms for data collection without direct interviews, and insufficient time for comprehensive data collection and literature review. Contribution: This study provides empirical evidence for human resource management practitioners and organizational leaders in Indonesian professional certification institutions, contributing to the field of organizational behavior and performance management by demonstrating the significant relationships between competence, training, and motivation on employee performance.